Pengaruh Habits of Mind (Kebiasaan Pikiran) terhadap Ketahanmalangan Mahasiswa - Nurmala Dewi Qadarsih; Maimunah Maimunah; Finata Rastic Andrari (SAP (Susunan Artikel Pendidikan), 2022)
The adversity of students in dealing with current problems is felt to have decreased significantly. For this reason, researchers feel the need to look for one aspect that can increase students adversity, namely through the habit of mind variable. The purpose of this research is to determine the direct effect of habits of mind on the adversity question among students of informatics engineering study program at the University of Indraprasta PGRI. A sample of 100 students was taken using purposive sampling technique from 5th semester students at Indraprasta PGRI University. The samples collected by questionnaire technique. The method used in this study was a purposive sampling survey method, which was one type of sampling commonly used in scientific research. The research showed there was a significant direct effect of habits of mind on the adversity question of the 5th semester students of Indraprasta PGRI. This was evidenced by t count (10,066) > t tablel (1,980) with a significance level of 5 %.. This research can be recommended to improve the adversity question by increasing their habits of mind. In addition, the results of this study can also be developed by recommending indicators of Habits of Mind into aspects of learning in the classroom.